Genotoxic and cytotoxic potential of whole plant extracts of Kalanchoe laciniata by Ames and MTT assay - Sharif, Ali; Akhtar, Muhammad Furqan; Akhtar, Bushra; Saleem, Ammara; Manan, Maria; Shabbir, Maryam; Ashraf, Muneeb; Peerzada, Sohaib; Ahmed, Shoaib; Raza, Moosa (Technische Universität Dortmund, 2017)
Lack of data on safety of herbal medicines have endangered human health and life. The present study evaluated the genotoxic and mutagenic effect of Kalanchoe laciniata to access the safety and usefulness of the medicinal plant. Aqua-methanolic and n-hexane extracts of K. laciniata were evaluated for the genotoxic potential using Ames assay and cytotoxicity was evaluated using MTT assay. Ames assay was conducted using two strains of Salmonella typhimurium TA-100 and TA-102 whereas MTT assay was performed on baby hamster kidney cell line BHK-21. Aqua-methanolic extract of K. laciniata exhibited significant mutagenicity when exposed to TA- 102 strain with a mutagenic index of 50.66 and 54.74 at maximum dose 150 mg/plate. The extract was also muta- genic to TA-100 strain but to a lesser extent. M.I of n-hexane extract was 12.15 and 15.51 for TA-100 and TA- 102 respectively. n-hexane extract was mutagenic but little difference was observed between results of two strains. Both extracts were found to be cytotoxic with an IC50 of 321.9 and 638.5 µg/mL for aqua-methanolic and n-hexane extracts respectively. On the basis of results it was concluded that aqua-methanolic and n-hexane extracts of K. mutagenic and cytotoxic potential. It is suggested to explore the plant further to evaluate its safety in rodents and other species.
EXCLI Journal;Vol. 16 2017
Keywords: Kalanchoe laciniata; mutagenicity; cytotoxicity; ames assay; Salmonella typhimurium; 610